Ngaji Lowo: Strategi Peningkatan Pemahaman Agama Pada Masyarakat Di Majelis Ta’lim Babussalam Gondek Mojowarno Jombang Jawa Timur - Mar’atul Azizah; Sunardi Sunardi (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, This study examines the Strategy for Improving Understanding of Religion in Communities in the Tausslim Babussalam Gondek Mojowarno Jombang East Java. The approach in this research is a qualitative case study type. In data collection methods used for participatory observation, in-depth interviews and documentation. Data analysis techniques using data collection, data reduction, data presentation and drawing conclusions. To check the validity of the data used research extension, observation persistence, and triangulation. The results of this study are the planning, implementation and evaluation system of lowo recitation in the Tausslim Babussalam Gondek Mojowarno Jombang, East Java Ngaji Lowo/Santri Kalong in the Babussalam Gondek Ta'lim Assembly Mojowarno Jombang namely holding meetings, structuring learning schedules, implementing activities, concerning facilities Temporary infrastructure evaluation forms that are carried out first take the form of tests, such as: students are directly asked one by one by Pak Kyai about about the books that have been studied, practice reading books one by one, mutholaah books, tahlil practices, qiroah exercises and khitobah exercises with students others. The second evaluation is in the form of non-tests, such as: deliberation with other students, interacting directly with the community, participating in the Qur'anic sermons in the mosque and being shared with the surrounding community.Keywords: Koran Lowo, Strategy, and Religion